Breast Microcalcifications as Type Descriptors to Stratify risk of Malignancy: a Systematic Review and Meta-Analysis of 10665 Cases with Special Focus on Round/Punctate Microcalcifications - Rominger, M.; Wisgickl, C.; Timmesfeld, N. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2012)
Purpose: To use a systematic review and meta-analysis to determine the predictive value of five suspicious type descriptors of microcalcifications, with special focus on round/punctate microcalcifications because of controversy.Materials and Methods: We performed a literature search using three databases and one search engine. We screened citations for malignancy rates of type descriptors. We regarded malignancy rates below 2 % (BI-RADS 3) and above 95 % (BI-RADS 5) as clinically significant threshold values for suspicion (BI-RADS 4). Results: Forty studies from 14 countries with a total of 10,665 microcalcification lesions were included. The pooled malignancy rates were: coarse heterogeneous, 13 % (95 % confidence interval (95 %-CI): 7 – 20 %); amorphous or indistinct, 27 % (95 %-CI: 21 – 33 %); pleomorphic, 50 % (95 %-CI: 43 – 58 %); linear, 78 % (95 %-CI: 68 – 86 %). The pooled malignancy rate of all round/punctate microcalcifications was 9 % (95 %-CI: 6 – 13 %), for the subgroup follow-up it was 0,5 % (95 %-CI: 0.08 – 2.57 %), and with histological verification it was 14 % (95 %-CI: 11 – 19 %). Woman selection and consideration of additional suspicious image findings were reasons for between-study heterogeneity. Addition of ACR distribution descriptors diversified risk stratification, but did not alter BI-RADS assessment category.Conclusion: All suspicious type descriptors including round/punctate microcalcifications as well as combinations of type with suspicious distribution descriptors fell into BI-RADS assessment category 4. Exclusion of suspicious adjunct factors can direct clustered, round/punctate microcalcifications to a lower BI-RADS assessment category.
Keywords: breast; mammography; calcifications/calculi